The influence of implementation school operational assistance policy towards students Achievement - Sopyan Sopyan; Rifdan Rifdan; Muhammad Guntur (Universitas Negeri Makassar, 2021)
The government issued a policy of BOS (School Operational Assistance) aims to maximize the performance of schools to meet all school needs that can support student learning achievement which ultimately results in good and quality educational goals. The purpose of this study was 1) to find out the implementation of the School Operational Assistance (BOS) policy at SMK Negeri 5 Pangkep in Pangkejene and Kepulauan Regency, 2) to determine the level of student achievement in SMK 5 Pangkep in Pangkejene and Kepulauan Regency, 3) to determine the effect of the policy School Operational Assistance (BOS) on the level of student achievement in SMK 5 Pangkep in Pangkejene and Kepulauan Regency. This research uses a quantitative approach, with a population of 305 people and a sample of 62 respondents. Data collection techniques through observation, angekt, interviews and documentation. Data analysis techniques in this study used descriptive analysis and inferential statistical analysis. The results showed that 1) The implementation of BOS policy of the four indicators ranging from communication, resources, disposition, and bureaucratic structure as a whole was considered to be going well which reached a percentage of 77.33 percent, 2) Student achievement in SMK Negeri 5 Pangkep from cognitive, psychomotor, and affective indicators which overall of the three indicators reached report card which is 4 or 82.17 percent considered good. 3) The implementation of BOS policy has a moderate and positive influence on student achievement with an R square (r2) score of 42.10 percent. The influence of the management of BOS funds on student achievement in SMK 5 Pangkep has a positive impact because of the availability of facilities needed by students even though it is not adequate or complete as a whole, but its management has been maximally used in improving student achievement. In addition, with the BOS funds the costs incurred by parents of students are also aided so that there is encouragement so that their children can increase education at school and develop the talents and interests of the students.